EPISTEMOLOGI TAFSIR NUSANTARA: Studi Atas Tafsir Fayd al-Rahman Karya K.H. Shaleh Darat - Didik Saepudin (UIN Siber Syekh Nurjati Cirebon, 2019)
K.H. Shaleh Darat was a 19th-century Javanese cleric who almost escaped the observation of the history of the Islamic archipelago. His concern for lay Muslims has made him have the courage to break the norm by translating and interpreting the Qur'an using the writings of pegon (Javanese-Arabic script). According to him, useful knowledge does not have to be in Arabic that seems